PEMENUHAN HAK POLITIK NARAPIDANA RUTAN KELAS IIB PEKANBARU PADA PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR RIAU TAHUN 2018 - Fauzi, Rioko; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to explain the fulfillment of political rights of prisoners and the factors that cause the political rights of most prisoners of Class IIB Pekanbaru to fulfill their political rights during the 2018 Riau Governor and Deputy Governor Election.This research was conducted at Class IIB Rutan Pekanbaru, Pekanbaru City, Riau Province. The method used is a qualitative research method with descriptive research type, analysis. The technique used in data collection is by conducting in- depth interviews with several informants as well as from other sources related to this research. The data obtained will be reduced based on the needs, then collected and concluded to be presented. This research uses the theory of democracy and electoral management.The results of this study indicate that the law has protected prisoners in fulfilling political rights (the right to vote). In holding the election for the Governor and Deputy Governor of Riau in 2018, it is considered that it has not been carried out properly and optimally. Because there are still many prisoners who have not received the right to be able to vote in the election for the Governor and DeputyGovernor. There are still problems found in the field due to several factors, both from internal sources such as the absence of appropriate regulations from the KPU in fulfilling the political rights of prisoners. Then external factors such as the narrow space for prisoners to take care of various requirements to be able to exercise their political right to vote.Keywords: Political Rights, Prisoners, Election for Governor and DeputyGovernor.